Genetic Polymorphism at CCL5 Is Associated With Protection in Chagas’ Heart Disease: Antagonistic Participation of CCR1+ and CCR5+ Cells in Chronic Chagasic Cardiomyopathy - Batista, Angelica Martins; Alvarado-Arnez, Lucia Elena; Alves, Silvia Marinho; Melo, Gloria; Pereira, Isabela Resende; Ruivo, Leonardo Alexandre de Souza; da Silva, Andrea Alice; Gibaldi, Daniel; da Silva, Thayse do E. S. Protásio; de Lorena, Virginia Maria Barros; de Melo, Adriene Siqueira; de Araújo Soares, Ana Karine; et al. (Frontiers in Immunology, 2018)
Chronic cardiomyopathy is the main clinical manifestation of Chagas disease (CD), a disease caused by Trypanosoma cruzi infection. A hallmark of chronic chagasic cardiomyopathy (CCC) is a fibrogenic inflammation mainly composed of CD8+ and CD4+ T-cells and macrophages. CC-chemokine ligands and receptors have been proposed to drive cell migration towards the heart tissue of CD patients. Single nucleotide polymorphisms (SNPs) at CC-chemokine ligand and receptor genes may determine protein expression. Herein, we evaluated the association of SNPs in the CC-chemokines CCL2 (rs1024611) and CCL5 (rs2107538, rs2280788), and the CCL5/RANTES receptors CCR1 (rs3181077, rs1491961, rs3136672) and CCR5 (rs1799987) with risk and progression towards CCC. We carried out a cross-sectional association study in 406 seropositive patients from endemic areas for CD of the State of Pernambuco, Northeast of Brazil. The patients were classified as non-cardiopathic (A, n = 110) and cardiopathic (mild, B1, n = 163; severe, C, n = 133). Serum levels of CCL5 and CCL2/MCP-1 were elevated in CD patients, but neither associated with risk/severity of CCC nor with SNP genotypes. After logistic regression analysis with adjustment for the covariates gender and ethnicity, CCL5 -403 (rs2107538) CT heterozygotes (OR = 0.5, P-value = 0.04) and T carriers (OR = 0.5, P-value = 0.01) were shown to be associated with protection to CCC. To gain insights into the participation of the CCL5-CCR5/CCR1 axis in CCC, mice were infected with the Colombian T. cruzi strain. Increased CCL5 concentrations were detected in the cardiac tissue. In spleens, frequencies of CCR1+ CD8+ T-cells and CD14+ macrophages were decreased, while frequencies of CCR5+ cells were increased. Importantly, CCR1+CD14+ macrophages were mainly IL-10+, though CCR5+ were mostly TNF+. CCR5-deficient infected mice presented reduced TNF concentrations and injury in the heart tissue. Selective blockage of CCR1 (Met-RANTES therapy) in ccr5-/- infected mice supports a protective role for CCR1 in CCC. Further, parasite antigen stimulation of CD patient blood cells increased the frequency of CCR1+CD8+ T-cells and CCL5 production. Collectively, our data support that a genetic variant of CCL5 and CCR1+ cells may confer protection to Chagas’ heart disease, identifying the CCL5-CCR1 axis as a target for immunostimulation.